Strategic Orientation and Organizational Ambidexterity Practices of Mobile Communication Firms in Port Harcourt - Enyindah, Wegwu, Macaulay (International Journal of Emerging Trends in Social Sciences, 2019)
The purpose of the study was to investigate the relationship between strategic orientation and organizational ambidexterity practices of mobile communication firms in Port Harcourt. One research question was asked deemed very important and one hypothesis was also tested. A sample size of 112 was used from a population of 162 employees which consisted of 4 top level managers, 37 middle level managers and 121 supervisors in the regional offices of four mobile communication firms in Port Harcourt. A cross-sectional survey technique was adopted, questionnaire distributed and data generated were analyzed using Pearson Product Moment Correlation Coefficient. Result revealed that strategic orientation has significant relationship with organisational ambidexterity. It was therefore recommended that strategic orientation of the firms should be predicted on the dynamics of market competitiveness and the environment to effectively influence organizational ambidexterity.